Effect of Morphology on Electrochemical Performance of Chalcopyrite Cathode. Issue 2 (February 2020) - Ding, Wei; Bi, Dapeng; Shen, Jie
Abstract: Chalcopyrite was synthesized with various reaction precursors and solvents, and plate-, rod-, and sphere-like chalcopyrite can be obtained. Our results show that rod-like chalcopyrite has higher discharge capacity, better rate capacity and cycle performance than others.